2016
DOI: 10.1161/circulationaha.116.021347
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic Targeting of Ca v β2 Overcomes Dysregulation of the L-Type Calcium Channel Density and Recovers Cardiac Function

Abstract: Original research article BACKGROUND: L-type calcium channels (LTCCs) play important roles in regulating cardiomyocyte physiology, which is governed by appropriate LTCC trafficking to and density at the cell surface. Factors influencing the expression, half-life, subcellular trafficking, and gating of LTCCs are therefore critically involved in conditions of cardiac physiology and disease. METHODS:Yeast 2-hybrid screenings, biochemical and molecular evaluations, protein interaction assays, fluorescence microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…3B and table S4). Improvement of molecular and cellular defects associated with diabetic cardiomyopathy was achieved as a result of the direct targeting of MP to LTCC (24), including restoration of LTCC protein levels ( Fig. 3C and fig.…”
Section: Efficacy Of Inhaled Caps Loaded With a Therapeutic Mp To Impmentioning
confidence: 99%
See 2 more Smart Citations
“…3B and table S4). Improvement of molecular and cellular defects associated with diabetic cardiomyopathy was achieved as a result of the direct targeting of MP to LTCC (24), including restoration of LTCC protein levels ( Fig. 3C and fig.…”
Section: Efficacy Of Inhaled Caps Loaded With a Therapeutic Mp To Impmentioning
confidence: 99%
“…All animals were obtained from the Charles River Laboratories. Therapeutic treatment of mice was performed as follows: Type 1 diabetes was induced in adult C57B6/J male mice by intraperitoneal injection of STZ (50 mg/kg per day) for five consecutive days as previously described (24). Seven days after the last STZ injection, whole blood was obtained from the mouse tail vein and glucose levels were measured using the Accu-Chek Aviva blood glucose monitoring system (Roche).…”
Section: Experimental Animals Micementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a number of cardiac pathologies, there is a decreased expression of CaV1.2 VDCC [29]. A recent study has demonstrated that the physiological expression of CaV1.2 at the plasma membrane depends on Akt-dependent phosphorylation of β2 at its C-terminus, allowing binding of β2 with CaV1.2 [30]. Another actor, Kir/Gem, also regulates the association between CaV1.2 and β subunits.…”
Section: Targeting Voltage-dependent Calcium Channel Interactionsmentioning
confidence: 99%
“…Therefore, further studies addressing pharmacokinetic analysis are required; since supraphysiological levels of Ca v α 1.2 and Ca v β 2 exert detrimental effects regarding myocyte function, effects which are beyond the linear correlation between Ca v α 1.2 and Ca v β 2 are highlighted by preliminary data [47]. Moreover, several tissue-specific elements should be tackled; since Ca v β 2 has a broad tissue distribution, not being limited to cardiac tissue, thus possibly generating several issues, difficulty which might be overcome by using functionalized nanoparticles [47, 48] allow specific cardiac delivery.…”
Section: Future Directions For Diagnosis and Potential Treatment Tmentioning
confidence: 99%